A Feminist Stylistic Analysis of Doris Lessing's The Fifth Child (1988) - Zahra Rahimnouri; Azra Ghandehariun (Journal of Language and Literature, 2020)
This study is a feminist stylistic analysis of The Fifth Child (1988). This study attempts to combine literary and linguistic theories by using the feminist stylistic approach of feminist stylisticians. This study investigates the lexico-semantic items in narration, gendered sentences, and items such as metaphors, adjectives, and their frequency, grammar, and different lexical items such as those related to colors. Also, Short's ideas about powerful/ powerless were used to discuss the dynamic of power in the relationship between Harriet and David. Through this analysis, female ideologies of the novel were also analyzed and discussed. Feminist stylistic theories were applied to explain how Harriet's language and description represent her passivity, obedience, and dependence. This study evaluates the grammatical and lexical components of the 'female sentence' to discover that female writing is unique and different from male writing. We inferred the author’s feminist style through how Harriet is described as a traditional, old-fashioned, powerless, and subordinated woman. Harriet accepts the dominance of men and persuades readers to sympathize Harriet whom everyone blames for giving birth to an abnormal child who causes too much trouble for everyone.